2016
DOI: 10.5888/pcd13.150501
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Chronic Conditions and Use of Complementary and Alternative Medicine Among US Adults: Results From the 2012 National Health Interview Survey

Abstract: IntroductionMore than 25% of American adults report having 2 or more chronic conditions. People with chronic conditions often use complementary and alternative medicine (CAM) for self-care and disease management, despite a limited evidence base.MethodsData from the 2012 National Health Interview Survey (NHIS) (n = 33,557) were analyzed to assess associations between presence of multiple chronic conditions (n = 13) and CAM use, using multivariable relative risk and linear regressions weighted for complex NHIS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 21 publications
5
79
1
4
Order By: Relevance
“…The weighted prevalence of MCC in 2014–2015 was 27.3%. Although the prevalence of having 1 chronic condition in our study (24.4%) was almost similar to the prevalence in a US study in 2012 (22.3%) (18), the prevalence of MCC was lower in our study (27.3%) than in the US study (33.8%). The prevalence of MCC was lower in our study also than the prevalence (37.2%) in a study conducted in Yorkshire, England, between 2010 and 2012, among a population aged 24 or older (11).…”
Section: Discussionsupporting
confidence: 70%
“…The weighted prevalence of MCC in 2014–2015 was 27.3%. Although the prevalence of having 1 chronic condition in our study (24.4%) was almost similar to the prevalence in a US study in 2012 (22.3%) (18), the prevalence of MCC was lower in our study (27.3%) than in the US study (33.8%). The prevalence of MCC was lower in our study also than the prevalence (37.2%) in a study conducted in Yorkshire, England, between 2010 and 2012, among a population aged 24 or older (11).…”
Section: Discussionsupporting
confidence: 70%
“…In the current study, individuals with no chronic disease were found to use dietary supplements at higher rates, and when other characteristics were examined, it was determined that BMI did not affect dietary supplement use, while poeple who regularly exercised and who attended routine check-ups more often preferred to use dietary supplements. In previous studies conducted with different groups, individuals with chronic diseases were reported to use CAM methods at higher rates (Loera et al, 2007;Erdogan et al, 2013;Falci et al, 2016;Erdogan et al, 2017). In the present study study, individuals with no chronic disease were found to more commonly use dietary supplements.…”
Section: Discussionsupporting
confidence: 51%
“…These differences could be attributed to many reasons, including cultural, social, economic and technological trends. Considering observation that people with multiple chronic conditions have an increased likelihood of using CAM, overall aging of the population and increasing prevalence of chronic diseases, it is likely to expect that CAM approaches will become even more popular in the future [12,[23][24][25][26][27][28]. In recognition of the widespread popularity of CAM, leading academic institutions have started to incorporate CAM into medical education, clinical practice and research [29,30].…”
Section: Discussionmentioning
confidence: 99%